How embankment influences coastal livelihood in the context of climate adaptation – a case study of Indian Sundarban Delta. Issue 3 (31st March 2022) - Saha, Senjuti; Hazra, Somnath; Ghosh, Tuhin
Abstract : Purpose: The decision of livelihood based on the embankment characters is essentially multivariate. Making an effort to do the bivariate modelling may eliminate the useful socio-economic information in the interdependent and simultaneous adaptation choices (Dorfman, 1996). Hence, the more appropriate method is multiple-choice decisions to livelihood adoption based on the embankment category. The purpose of this study is to find out whether the inhabitants of Sundarban really consider embankment as their "lifeline", what they think about its sustainability and what the outer world thinks about the embankment. Design/methodology/approach: To analyse this study, the multinomial logit (MNL) model has been used. This model gives a platform to study the influence of the factors on livelihood choice decisions. In this MNL model, the livelihood decisions are categorized based on their primary livelihood status at the survey. Thus, the choice of livelihood among individuals is explained in terms of the livelihood and the household characteristics. Findings: This result can possibly explain the fact that increasing population or man power and increasing annual income and protection from embankment failure may reduce the need to choose any other form of economy apart from the indigenous one, as the society is dominated by farmers who own very small plots of land and face consequences like crop failure every year because of natural calamities. A unit increase in annual income would result in a 0.53% decrease in the probability of choosing labourer as occupation and 0.57% decrease in the probability of choosing fishing/"meen" collection as occupation. Research limitations/implications: The district is vast enough, and it is difficult to study all the blocks. Initially, nine blocks were identified as affected blocks from various literature reviews. Those blocks are Sagar, Patharpratima, Kultali, Gosaba, Kakdwip, Canning I, Canning II, Namkhana and Basanti. Pilot surveys were done to all those nine blocks identified above. After such a long and rigorous procedure, blocks were verified from available secondary data. Villages from vulnerable and less vulnerable parts of the later mentioned blocks are picked up as purposive sample, and household surveys are done on the basis of random sampling. Social implications: If the year of schooling is enhanced, then the tertiary sector gets benefited, but the indigenous society of Sundarban cannot depend on such a sector as the scope for development is very limited. Consequently, policies aiming at promoting adaptation to challenged livelihood need to emphasize the crucial role of providing basic needs for better production techniques; and more investment in this sector will surely enable villagers to adapt cultivation following age-old tradition. Originality/value: The study uses the MNL model to investigate the factors guiding household choices of different occupational adaptation methods, and cultivation is found to be the automatic choice for the inhabitants of Sundarban. Cultivation is impossible without embankment. Thus, the embankment in Sundarban is considered, as "lifeline" is established. So it can be said that livelihood in this region depends on the stability of embankment. This age-old structure is susceptible to vulnerability because of its unscientific construction and improper maintenance. The main objective of this study is to find out whether the inhabitants of Sundarban really consider embankment as their "lifeline", what they think about its sustainability and what the outer world thinks about the embankment.